Concentration, risk assessment, and source identification of heavy metals in surface sediments in Yinghai: A shellfish cultivation zone in Jiaozhou Bay, China - Liu, Xiaomeng; Zhang, Lei; Zhang, Lei (Marine pollution bulletin, 2017)
To identify the affection of shellfish cultivation on sediment conditions in Yinghai shellfish cultivation zone in Jiaozhou Bay, the concentration, sources, and the potential ecological risk of heavy metals was identified. Results show the range of Cu, Zn, Pb, Cd, Cr, Hg, As and Mn are 10.15–29.98, 35.95–111.22, 12.44–27.68, 0.08–0.22, 18.03–82.32, 0.04–0.13, 4.02−7.72 and 574.07–839.33mg·kg−1. Shellfish cultivation influences heavy metal content to some extent. Principal component analysis suggests the accumulation of Zn, Mn, and Cu mainly results from agricultural and industrial actions, Pb from traffic pollution, and Hg from coal combustion. According to the potential ecological index, there is medium and higher ecological risk of contamination by Hg and Cd, which indicates that the study area suffers from varying degrees of heavy metal pollution. •Heavy metal pollution in sediments in Jiaozhou Bay, China has reached concerning levels.•The conditions of shellfish cultivation affect the sediment environment in this semi-enclosed bay.•The enrichment of Hg in sediments mainly comes from coal combustion in wetland ecosystems in China.